Influence of early weaning and winter protein supplementation on weight and condition score of spring-calving beef cows grazing native tallgrass prairie - K.W. Harborth; Donald A. Llewellyn; T.T. Marston (Kansas Agricultural Experiment Station Research Reports, 2005)
Ninety-two pregnant, mature, spring-calving cows grazing low-quality tallgrass-prairie were used to determine if early weaning of calves reduces the supplementation cost during the subsequent winter. Calves were weaned on June 23, 2003, (early weaning) or October 15, 2003, (fall weaning). Cows were assigned to winter feeding groups and fed one of two amounts of a common soybean meal-milo supplement (45% crude protein; dry matter basis). The two supplementation amounts were fed three times weekly and were prorated to 4 lb/day and 2.8 lb/day. The four treatment groups were: 1) early weaning - 4 lb/day supplement, 2) early weaning - 2.8 lb/day supplement, 3) fall weaning - 4 lb/day supplement, and 4) fall weaning - 2.8 lb/day supplement. Cows were supplemented from November 14, 2003, through calving in early March 2004. Cows with calves weaned early were initially heavier and had higher initial body condition scores than did cows that were weaned in the fall. Although losses of body weight and body condition through the winter were greater for early-weaning cows than for fall-weaning cows, final body weights and body condition scores were still greater for the early-weaning cows than for the fall-weaning cows. Supplementation with 4 lb/day led to less body weight loss over the winter and heavier final body weights than did supplementation with 2.8 lb/day, but final body condition score and body condition score loss over the winter were not affected by the amount of winter supplementation. Cow-calf producers can balance responses to early weaning and to winter supplementation to target appropriate cow weights and body condition scores at calving.
Keywords: Cattlemen& #x27; s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; Early weaning; Winter protein; condition score; Native tallgrass